Multilevel Governance, Decentralization and Environmental Prioritization: How is it working in rural development policy in Scotland? - Yang, A.L.; Rounsevell, Mark D.; Haggett, C. (Wiley, 2015)
Adopting a ‘multilevel’ governance system and environmental prioritization for the Rural Development Policy (RDP) in Europe are key actions recommended by the European Commission. Member States can decide how and to what extent these actions are incorporated into their RDP design. Through 61 semi‐structured in‐depth interviews with institutional stakeholders, this study assesses the application of these recommendations in RDP in Scotland. The findings indicate that many barriers to effective implementation and environmental prioritization exist due to rigid centralized policy controls. A lack of regionalized autonomy has hindered the ability of regional actors to effectively prioritize local needs. For future policy design, a successful multilevel governance system will require a clearer link between central regulatory requirements and how these link to practical policy implementation. In addition, recognizing an emphasis on ‘policy process’ there will be trade‐offs in effectiveness by outweighing consideration of actual policy outcomes. Copyright © 2015 John Wiley & Sons, Ltd and ERP Environment